Effect of feedforward control combined with tracking method on reducing the incidence of blockage of intravenous indwelling needle in perioperative patients (前馈控制追踪法在降低围手术期患者静脉留置针堵管率中的效果) - ZHANG Jianfang (张建芳); SHI Lihua (施丽华); LIN Yiqing (林依青); FENG Qi (冯绮); CHEN Qiyu (陈麒羽); LI Liqin (李立勤) (中西医结合护理)
Objective To investigate the effect of feedforward control combined with tracking method on reducing the incidence of blockage of intravenous indwelling needle in perioperative patients. Totally 852 patients who received intravenous infusion therapy were recruited and divided into two groups according to the odd-even number of admission: 424 patients with odd number in the control group and 428 patients with even number in the observation group. The control group received routine nursing management and catheter maintenance, the observation group adopted feedforward control combined with tracking method. The incidence of blockage of intravenous indwelling needle, indwelling time and incidence of redness and swollen at puncture site were compared between two groups. Results The indwelling time of intravenous indwelling needle in the observation group was higher than that of control group (P＜0. 01). A lower incidence of blockage of intravenous indwelling needle and lower incidence of redness and swollen at puncture site were reported in the observation group than that in the control group, respectively(P＜0. 01). Conclusion The feedforward control combined with tracking method is potentially effective to reduce the incidence of blockage of intravenous indwelling needle, prolong the indwelling time, reduce the pain at puncture site and improve the comfort level of patients during the treatment. (目的 探讨运用前馈控制联合追踪方法降低围手术期患者静脉留置针堵管率的效果。方法 选取苏州市立医院北区2021年3月—11月收治的852例患者为研究对象, 均接受静脉输液治疗。根据患者入院先后顺序分组, 单号纳入对照组(n=424), 双号纳入观察组(n=428)。对照组落实常规护理管理, 观察组引入前馈控制策略和追踪方法。比较两组静脉留置针堵管发生率、静脉留置针留置时间和穿刺部位红肿发生率。结果 观察组静脉留置针留置时间长于对照组, 差异有统计学意义(P＜0. 01)。观察组静脉留置针堵管发生率和穿刺部位红肿发生率均低于对照组, 差异有统计学意义(P＜0. 01)。结论 前馈控制联合追踪方法能够降低静脉留置针堵管风险, 延长静脉留置针留置时间, 减轻患者疼痛, 提升舒适度。)